2012
DOI: 10.1152/ajpcell.00396.2011
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium-independent phospholipase A2γ in modulation of aqueous humor drainage and Ca2+ sensitization of trabecular meshwork contraction

Abstract: Pattabiraman PP, Lih FB, Tomer KB, Rao PV. The role of calcium-independent phospholipase A 2␥ in modulation of aqueous humor drainage and Ca 2ϩ sensitization of trabecular meshwork contraction. Am J Physiol Cell Physiol 302: C979 -C991, 2012. First published January 11, 2012; doi:10.1152/ajpcell.00396.2011.-The contractile and relaxation characteristics of trabecular meshwork (TM) are presumed to influence aqueous humor (AH) drainage and intraocular pressure. The mechanisms underlying regulation of TM cell con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…PLA 2 Assay-PLA 2 activity was measured in COS-1 cell extracts using a PLA 2 activity assay kit according to the manufacturer's instructions and as described previously (42). In this assay, hydrolysis of arachidonoyl thiophosphatidylcholine at the sn-2 position by PLA 2 releases a free thiol that is detected by 5,5Ј-dithio-bis-2-nitrobenzoic acid.…”
Section: Methodsmentioning
confidence: 99%
“…PLA 2 Assay-PLA 2 activity was measured in COS-1 cell extracts using a PLA 2 activity assay kit according to the manufacturer's instructions and as described previously (42). In this assay, hydrolysis of arachidonoyl thiophosphatidylcholine at the sn-2 position by PLA 2 releases a free thiol that is detected by 5,5Ј-dithio-bis-2-nitrobenzoic acid.…”
Section: Methodsmentioning
confidence: 99%
“…42,44,80 In addition, enzymes generating these lysolipids were found to influence AH outflow and IOP. 43,81 There is also some evidence of dysregulation of LPA production in the AH and optic nerve head of glaucoma patients. 43,82,83 In addition, these bioactive lipids have been shown to play a critical role in the expression of ECM and a-smooth muscle actin.…”
Section: 63mentioning
confidence: 99%
“…111 Very recently, we not only confirmed the distribution pattern of 2 isoforms of calcium-independent phospholipaseA2 (iPLA2b and iPLA2g) in human TM and cultured TM cells, but also established their role in regulation of AH outflow facility. 81 Using isoform-specific small molecular inhibitors of iPLA2 (S-Bromoenol lactone) and (R-Bromoenol lactone), it has been demonstrated that iPLA2g plays a significant role in the regulation of TM cell contractile properties, cell shape, and cell adhesive interactions by controlling MLC phosphorylation. 81 These changes appear to be mediated by the signaling activities of Rho GTPase, PKC, and arachidonic acid in TM cells.…”
Section: Raomentioning
confidence: 99%
See 2 more Smart Citations